ANALISIS PENGGUNAAN METODE INDEX TIME SERIES UNTUK MENILAI KINERJA KEUANGAN PT. ADARO ENERGY TBK PERIODE TAHUN 2021-2023 - Mustofa adin; Roy Irawan (Universitas Prof.Hazairin,SH Bengkulu, 2024)
This study aims to assess and analyze the Financial Performance of PT. Adaro Energy Tbk using trend analysis. Trend analysis helps identify the direction of a company’s values by comparing them to a base year, which in this case is 2021. The research relies on quantitative daa derived from the company’s financial reports, particulary the balance sheet and income statement. These financial statements are converted into percentages to better understand the trends. The analysis reveals a decline in most key items or accounts in PT. Adaro Energy Tbk financial statements. Consequently, it can be concluded that the company’s financial performance, as assessed through the Time Series Index method, declined from 2022 to 2023